ARTERIAL HYPERTENSION AND ARRHYTHMIA (Spectrum Journal of Innovation, Reforms and Development, 2024)
According to the Framingham study, predictors of atrial remodeling may be an increase in the maximum duration and dispersion of the P wave measured on a standard ECG. Material and methods: A prospective case—control study included 41 patients (mean age 58.4 = 8.6 years). Retrospectively, according to the clinical and instrumental examination, stage I-II hypertension and the recurrent form of AF were verified. The control group consisted of 21 patients without hypertension and fp. Depending on the type of myocardial remodeling, 3 comparison groups were formed from patients with hypertension: the 1st group consisted of 18 patients with concentric LV remodeling (CLVR), the 2nd — 13 men and women with concentric LV hypertrophy (CLVH), the 3rd — 10 examined with eccentric LV hypertrophy (ELVH). Results and discussion: At the same time, attacks of AF and ventricular tachycardia persisted, were accompanied by calls from ambulance crews and, in 32.1% of cases, hospitalizations. However, subsequently, the appointment and constant intake of these drugs (the second year) allowed to reduce the number of arrhythmic complications, and after 2 years, patients noted a decrease in arrhythmia attacks, their better tolerability. Conclusions: In patients with arterial hypertension, long-term administration of β-blockers, angiotensin converting enzyme inhibitors, angiotensin receptor blockers and preductal reduces the risk of atrial fibrillation and ventricular arrhythmias.